PENGARUH DEFORMASI DINGIN DAN SURFACE MECHANICAL ATTRITION TREATMENT (SMAT) TERHADAP KEKERASAN, STRUKTUR MIKRO, DAN KETAHANAN KOROSI BAJA TAHAN KARAT AISI 316L - , NURFI AHMADI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
AISI 316L stainless steel has been widely used for biomedical material implants that needs high corrosion resistance and strength. Some methods have been developed in order to obtain its high performances, such as cold deformation and SMAT. This research aims to study the effects of combined methods (cold deformation and SMAT) in microstructure, hardness, and corrosion resistance of AISI 316L stainless steel. The dimension of specimen used in this investigation is 15 mm X 15 mm X 3mm. The cold deformation has been done to reduce the thickness by 47% using hydraulic press machine and followed by SMAT process. In SMAT process, 250 ball mill and motor speed of 1400 rpm are used with variation in dimension of 3.18 mm, 3.97 mm, 4.76 mm, and 6.35 mm. Besides, there is variation in duration: 5, 10, and 15 minutes. The results showed that cold deformation can increase the hardness about 127% and decrease the corrosion rate about 37%. Then combination cold deformation and SMAT can improve the hardness up to 16% and increase corrosion rate up to 40%.